Ogahiy’s Heritage – A Spiritual Treasure for the Present Generation - Baxtiyorova , Madina (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This article analyzes the rich literary, historical, and pedagogical heritage of Muhammad Rizo Erniyozbek oglu Ogahi, a prominent representative of the nineteenth-century Khorezm literary environment. It highlights his views on humanism, enlightenment, morality, devotion to the people, and the upbringing of a well-rounded individual. The article also examines Ogahi’s translation activity and his contribution to the development of Uzbek classical literature. The study emphasizes the importance of Ogahi’s legacy in the spiritual and moral education of the present generation.